Department for Regional Development - Transport NI in the matter of a public inquiry into York Street Interchange : Public Inquiry Before : Mr J Robb (inspector) and Mr Jack Cargo (assistant inspector), Thursday 12th November 2015, Taken at : Assembly buildings conference centre Fisherwick Place Belfast, BT1 6DW.: Public Inquiry Before : Mr J Robb (inspector) and Mr Jack Cargo (assistant inspector), Thursday 12th November 2015, Taken at : Assembly buildings conference centre Fisherwick Place Belfast, BT1 6DW. ([2016]) - Unknown
No abstract available